Intestinal occlusion due to strangulation of thin ansa in peritoneal sac of left external oblique hernia, spontaneously reduced in mass in the abdominal cavity - Loubejac, Armando (Cirugía del Uruguay, 2020)
Presented at session 4th October 1944